Deep Learning algorithm for the assessment of the first damage initiation monitoring the energy release of materials - Dario Santonocito; Dario Milone (Fracture and Structural Integrity)
Monitoring the energy release during fatigue tests of common engineering materials has been shown to give relevant information on fatigue properties, reducing the testing time and material consumption. During a static tensile test, it is possible to assess two distinct phases: In the first phase (Phase I), where all the crystals are elastically stressed, the temperature trend follows the linear thermoelastic law; while, in the second phase (Phase II), some crystals begin to deform, and the temperature assumes a non-linear trend. The macroscopic transition stress between Phase I and Phase II could be related to the limit stress that, if cyclically applied, would lead to material failure. Nowadays, it is impossible to distinguish the transition between Phase I and Phase II in an objective way. Indeed, it is up to the operator's experiences. This work aims to create a universal methodology that predicts the limit stress by assessing the change in temperature trend by adopting Neural Networks. A Deep Learning algorithm has been created and trained on experimental data coming from static tensile tests performed on several classes of materials (steels, plastics, composite materials). Once trained, the network can predict the transition temperature at which the first plastic deformation occurs within the material